ZINA DALAM PRESPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NO. 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - Anam, Afdolul; Anam, Syaiful (IQTISODINA, 2025)
This normative legal research aims to examine how Islamic law differs from Positive Law in Indonesia in this case Law No. 1 of 2023 concerning the Criminal Code regarding the act of adultery. Data sources obtained through comparative analysis studies. In general, there are differences in legal concepts between Islamic Law and Positive Law Law No. 1 of 2023 concerning the Criminal Code regarding the act of adultery, especially in terms of the punishment given. Islamic law provides a penalty of one hundred lashes for perpetrators of adultery, while Law No. 1 of 2023 concerning the Criminal Code states that adultery is a criminal act that can be punished with a sentence of 6 months to 1 year